Imaging of Pulmonary Infections, 1st Edition - Muller, Nestor L., Franquet, Tomas; Lee, Kyung Soo (Lippincott Williams & Wilkins, 2007)
Pulmonary infection is a major cause of morbidity and mortality. Over the last 2 decades, there has been not only an increase in the prevalence of various infections but also the recognition of several important new pathogens. Chest radiograph plays an essential role in the detection of parenchymal abnormalities consistent with pneumonia and in monitoring the response to treatment. Other roles for chest radiography include assessment of disease extent and detection of complications such as cavitation, abscess formation, and pleural effusion. Computed tomography (CT) is a valuable adjunct to chest radiography, particularly in the evaluation of pneumonia in the immunocompromised host, detection of complications such as empyema, and additional or alternative diagnoses, and as a guide to invasive diagnostic or therapeutic procedures. Imaging of Pulmonary Infections presents a brief, practical approach to the differential diagnosis of pulmonary infections based on their characteristic radiographic and CT manifestations. It discusses the value and limitations of chest radiography, indications for CT, optimal CT technique, and the role of intravenous contrast. The book describes and illustrates the characteristic imaging manifestations of the most common community-acquired pneumonias, nosocomial pneumonias, and the various infections seen in immunocompromised patients. It contains a large number of simple, practical tables that summarize the characteristic manifestations of bacterial, mycobacterial, fungal, and viral infections. The book is aimed at radiologists, pulmonary medicine physicians, and residents in radiology and pulmonary medicine, as well as internists and family practitioners taking care of patients with respiratory infection. It provides a simple, practical approach to the differential diagnosis of pulmonary infection and summarizes the value and limitations of imaging in the assessment of these patients.